Strategi Manajemen Pemasaran Pada UMKM RW 11 Semolowaru Menggunakan Metode Analisis SWOT Guna Meningkatkan Daya Saing - Ainan Salsabila; RA. Bulan Anugrah P; Tessa Mirella Dwivina; Sulthan Auliya Zhafran Fadhilah (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Micro, Small and Medium Enterprises have a significant role for the welfare of society. The purpose of this activity is to improve aspects of marketing management that have an impact on increasing sales. The long-term goal of this research is to build a management model that can be practically applied by MSMEs to support productivity and business development. In general, MSMEs business management (marketing, production, HR and finance) can be implemented by providing training to MSMEs actors. In its journey, MSMEs need to be monitored intensively, to always monitor the management they are doing. SWOT analysis is the right option to help MSMEs determine marketing strategies and project changes in the business environment. SWOT analysis can evaluate Strengths, Weaknesses which include internal factors in MSMEs, Opportunities and Threats which include external factors or competitors. Based on the SWOT analysis conducted, a strategy was obtained to provide training in all aspects, given the lack of knowledge possessed by SMEs. From this study, 4 marketing strategies were obtained for MSMEs to increase competitiveness, namely the S-O Strategy for MSMEs to innovate products to strengthen competitiveness, establish product characteristics, and aggressively carry out promotions and sales by utilizing technological developments with online sales. In the W-O strategy, MSMEs are required to always pay attention to market and consumer desires, determine market targets, and improve the quality of human resources. S-T strategy, MSMEs should make a prominent feature of the product and innovate in product promotion. In the W-T strategy, MSMEs players need to determine their target market, where and who is the target for their sales and pay attention to the wishes of the market and consumers to adapt their products.